Three‐dimensional hydrogen‐bonded framework structures in flunarizinium nicotinate and flunarizinediium bis(4‐toluenesulfonate) dihydrate. Issue 8 (15th August 2014) - Kavitha, Channappa N.; Yathirajan, Hemmige S.; Kaur, Manpreet; Hosten, Eric C.; Betz, Richard; Glidewell, Christopher
<x xml:space="preserve">Abstract</x> The structures of two salts of flunarizine, namely 1‐bis[(4‐fluorophenyl)methyl]‐4‐[(2E)‐3‐phenylprop‐2‐en‐1‐yl]piperazine, C26H26F2N2, are reported. In flunarizinium nicotinate {systematic name: 4‐bis[(4‐fluorophenyl)methyl]‐1‐[(2E)‐3‐phenylprop‐2‐en‐1‐yl]piperazin‐1‐ium pyridine‐3‐carboxylate}, C26H27F2N2+·C6H4NO2−, (I), the two ionic components are linked by a short charge‐assisted N—H...O hydrogen bond. The ion pairs are linked into a three‐dimensional framework structure by three independent C—H...O hydrogen bonds, augmented by C—H...π(arene) hydrogen bonds and an aromatic π–π stacking interaction. In flunarizinediium bis(4‐toluenesulfonate) dihydrate {systematic name: 1‐[bis(4‐fluorophenyl)methyl]‐4‐[(2E)‐3‐phenylprop‐2‐en‐1‐yl]piperazine‐1, 4‐diium bis(4‐methylbenzenesulfonate) dihydrate}, C26H28F2N22+·2C7H7O3S−·2H2O, (II), one of the anions is disordered over two sites with occupancies of 0.832 (6) and 0.168 (6). The five independent components are linked into ribbons by two independent N—H...O hydrogen bonds and four independent O—H...O hydrogen bonds, and these ribbons are linked to form a three‐dimensional framework by two independent C—H...O hydrogen bonds, but C—H...π(arene) hydrogen bonds and aromatic π–π stacking interactions are absent from the structure of (II). Comparisons are made with some related structures.